PENGEMBANGAN E-LEARNING BERBASIS SPIRITUAL UNTUK PELATIHAN DIGITAL MARKETING BAGI PELAKU UMKM HALAL DI KECAMATAN KOTO TANGAH KOTA PADANG - Achta Pratama, Fahmi; Andika Yufa, Nanda; Farhan Abimayu, Muhammad (Jurnal Dinamika Ekonomi Syariah, 2025)
This study aims to develop a spiritual-based e-learning platform for digital marketing training specifically designed for Halal MSMEs in Koto Tangah District, Padang City. This study uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to identify training needs, design an e-learning platform, and test its validity and practicality. This platform integrates digital marketing technical skills with Islamic spiritual values, such as honesty, justice, and responsibility. The validation results by learning media experts showed an average Aiken's V score of 0.918, reflecting the quality of visual design, layout, and intuitive navigation. Validation by digital marketing material experts obtained an average Aiken's V score of 0.924, indicating the relevance and depth of the material that is in accordance with the needs of MSMEs. Trials on 20 halal MSMEs showed an average practicality score of 88.75%, which is included in the "Practical" category. User responses included ease of use, time flexibility, and relevant spiritual values. The findings suggest that spiritual-based e-learning is effective in improving digital marketing competencies while strengthening ethical business practices that are in accordance with sharia principles. Recommendations include developing more intensive technical assistance for users with low digital literacy and evaluating the long-term impact on the performance of halal MSME businesses.